Feelings are like farts - Willard, Christopher (Psychologist); Wosiski, Tara (Henry Holy and Company, 2025)
A humorous picture book that helps readers understand that feelings, just like farts, are natural, universal, and fleeting. Feelings and farts are facts of life. We all have them! And we have to live with them, even when they're inconvenient, unpleasant, or surprising. They might come out of nowhere! It's definitely not a good idea to hold them in for too long. But among friends and family, they are usually no big deal. Striking a perfect balance of funny and factual, this charming picture book encourages young readers to accept their emotions (and their farts) without shame, even when they really stink.